Analisis Kekuatan AC-WC Bahan Fly Ash Batu Bara sebagai Pengganti Abu Batu dengan Metode Marshall - Nurdin, Ade; Erlangga, Erlangga; Nuklirullah, M. (Universitas Ibn Khaldun, 2023)
Abstract: The layers contained in flexible pavement, one of which is the Asphalt Concrete-Wearing Course (AC-WC) layer, is a layer that is quickly damaged compared to other layers, because this layer is located at the top and is directly related to environmental conditions and vehicle wheel loads. One of the efforts that can be made to increase the strength of the road pavement structure in the AC-WC layer is by utilizing waste material from burning coal as a substitute for stone ash. The material used is fly ash mixed with successive levels namely (0: 100), (25:75), (50:50), (75:25) and (100:0). The optimum asphalt content (OAC) used was 5.78%. Based on the results of the physical characteristic test using the Marshall test, the fly ash material to be used meets the required specifications. As it is affected by aggregate gradation, bitumen content and compaction process, the flow rate increases simultaneously. The stability value obtained from the asphalt content of 5.781% (10%) variant is 1097.0 kg, higher than the other variants. Only 2 sample variants meet VIM specifications. Obtained optimum asphalt value of 5.75% which is close to the initial optimal asphalt estimated. Key words: Coal Fly ash, Marshall Test, AC-WC, Optimum Asphalt Content, MQ-optimum